Theoretical proposal for the dynamical control of the nonlinear optical response frequency - Chotorlishvili, Levan; Sukhov, A.; Wimberger, Sandro; Berakdar, J. (Fluctuation and noise letters, 2013)
We propose theoretically a method for the control of the frequency of the nonlinear optical response of a model nonlinear medium driven by an electric field and suggest an experimental realization on the basis of isotropic LiF, or NaCl crystals and pulsed Nd glass laser. The theoretical background of the proposed optical control is the nonlinear resonance and the resonance overlapping which is typical for nonlinear systems. It is shown that by a proper choice of the parameters of the applied pulses a diffusive growth of the oscillation amplitude can be achieved resulting in a controlled switching of the system's frequency. The maximum frequency of the nonlinear response is identified to be proportional to the intensity of the applied noise. An experimental suggestion for particular materials is proposed.
Submitted on 1 Nov 2012
Gesehen am 16.04.2021